(untitled) (Journal of International Studies, 2020)
Citizens of ASEAN states appear to be increasingly involved, through Information Communication Technologies (ICTs), in pushing for greater openness and accountability of their political leaders and public institutions. In particular, ICTs afford citizens of ASEAN States and like-minded counterparts around the world in the human rights community to push for greater accountability of ASEAN’s human rights institutions. With the adoption of the ASEAN Charter in 2007, ASEAN states embarked on a process of crafting a regional ASEAN Intergovernmental Commission on Human Rights (AICHR), eighteen years after the World Conference on Human Rights in Vienna, Austria. While the World Conference had reaffirmed the universality of human rights, ASEAN states have moved grudgingly and gradually, egged on by greater global concern for human rights and by the pressures of globalization, towards the protection of human rights. The Terms of Reference (TORs) of the AICHR, adopted in July 2009 and favouring promotion rather than protection of human rights did not provide for an institutionalised role for the media. Subsequent drafting by AICHR of a proposed ASEAN Human Rights Declaration (AHRD) has excluded mainstream news media and civil society organizations (CSOs) from the process. In the absence of reporting and substantive reporting by most mainstream media in the region civil society, most importantly the new ICT based media, has played a vital role in seeking to advance the protection of human rights. This includes scrutiny of the specific rights that will be included in the forthcoming AHRD to ensure that international human rights standards are upheld and that ASEAN states honour their existing commitments under international instruments. The new media-environment provides a platform for a multitude of actors to disseminate human rights related information, to document human rights abuses and thereby enhance the protection of human rights in the region.